Praktik Kewirausahaan Sosial Berbasis Pelayanan kepada Para Difabel untuk Membentuk Insan Mandiri (Studi Kasus pada Yayasan Balai Karya Berkat di Getasan, Kabupaten Semarang - Darlene Gabriella Timotius; Hani Sirine (CV. Rumoh Aceh Publishing, 2026)
This study aims to describe the practice of social entrepreneurship based on services for persons with disabilities at the Balai Karya Berkat Foundation, Semarang Regency. The research stems from concerns over limited employment opportunities for persons with disabilities and the foundation’s efforts to foster self-reliance through social entrepreneurship activities. A qualitative approach with descriptive methods was employed. Data were collected through interviews, observations, and documentation involving four groups of informants: foundation administrators, employees, consumers, and persons with disabilities as training participants. The findings reveal that the foundation’s social entrepreneurship practices are carried out through preparation, implementation, and evaluation stages. Key enabling factors include sustainable funding, social legitimacy, transformative leadership, and participants’ internal motivation. Meanwhile, challenges involve limited managerial resources, technical constraints and workload intensity, and restricted access to business capital and marketing channels. Social entrepreneurship practices encompass program and facility preparation, training implementation, production, marketing and networking, and evaluation of self-confidence and economic contribution. These activities positively impact economic independence, enhance participants’ self-esteem, and promote broader social acceptance and engagement within the community.